Commandeering of the cellular HuR protein by alphaviruses affects the regulation of host post-transcriptional gene expression - Barnhart, Michael D., author; Wilusz, Jeffrey, advisor; Wilusz, Carol J., committee member; Laybourn, Paul J., committee member (Colorado State University. Libraries, 2013)
It was previously shown that cellular HuR protein binds to a U-rich region in the 3'UTR of Sindbis virus RNA resulting in stabilization of viral transcripts and increased replication efficiency. While the presence of this U-rich region is generally conserved among alphaviruses, a subset lacks a typical U-rich region. The 3'UTR of two alphaviruses - Ross River virus and Chikungunya virus - that do not contain a typical U-rich region were tested for HuR interactions by Electrophoretic Mobility Shift Assay. HuR protein bound these 3'UTRs with nanomolar affinities, similar to what was observed for the U-rich region of Sindbis virus. These observations demonstrate that the critical role for HuR-mediated viral RNA stabilization is likely a conserved property of most, if not all, members of the virus family. By analyzing deletion derivatives, we mapped the novel HuR binding sites in these two viruses to specific regions in their 3'UTR. Next, we uncovered four novel aspects of virus-host interaction and pathogenesis related to the high affinity interaction between the 3'UTR of alphaviruses and the cellular HuR protein. First, HuR protein, which is usually localized predominantly to the nucleus, dramatically accumulates in the cytoplasm during Sindbis virus (SinV) infection. Studies involving the transfection of constructs that express viral 3'UTR RNA fragments indicated that the mechanism of induction of HuR accumulation to the cytoplasm in infected cells is due to the viral RNA acting as a sponge for the protein. Second, HuR interaction with numerous cellular mRNAs was found to be drastically decreased during a SinV infection and was associated with dramatic destabilization of the cellular transcripts as determined by mRNA half-life analysis. Third, we found that the reduced amounts of free HuR during a SinV infection results in the increased targeting of mRNAs by miRNAs. Together, these data indicate that in the process of commandeering the cellular HuR protein for its own use, alphaviruses are also effectively destabilizing numerous cellular mRNAs. Interestingly, many of the cellular mRNAs affected by alphaviruses play key roles in inflammation, innate immune responses and other fundamental cellular processes. Finally, we observed a novel effect of SinV infection on alternative polyadenylation of cellular transcripts. This is likely a direct result of sequestration of the HuR protein in the cytoplasm by the virus, preventing the protein from influencing nuclear polyadenylation site choice. Intriguingly, SinV infection influences the poly(A) site choice of the HuR pre-mRNA, favoring a more translatable isoform to promote the overexpression of this viral host factor. Therefore, the alphaviral-induced alterations in cellular mRNA stability and polyadenylation identified in this thesis may play a very important but underappreciated role in pathogenesis.
Keywords: 3'UTR; alphavirus; HuR; mRNA stability; nuclear-cytoplasmic shuttling; protein-RNA interaction